Physico-Chemical Characterization of Sesame/Rapeseed Oil Mixtures - Maria Marudova; Asya Viraneva; Ginka Antova; Krastena Nikolova; Zhana Petkova; Olga Teneva (Applied Sciences)
The production of edible plant seed oil used in the food industry is increasing globally. More than 75% of lipids in the human diet come from edible vegetable oils. Among them, sesame oil has the highest resistance to oxidation, valuable physiological properties, and a unique flavor and aroma. However, sesame oil is more expensive than rapeseed oil, and often both oils are mixed to reduce costs. In this study, we performed a physical and physico-chemical analysis of sesame oil and sesame/rapeseed oil mixtures (5/95, 10/90, 30/70, 50/50, 70/30 and 90/10 w/w). The investigated oils were characterized based on their fatty acid composition, peroxide value, iodine value, phase transitions, refractive indices, color and UV–Vis adsorption. The fatty acid composition of mixtures made from sesame and rapeseed oils depended on the ratio of the two oils. Increasing the content of sesame oil in the mixtures resulted in a decrease in the levels of oleic and linolenic acids, while the levels of linoleic acid increased. A very good linear correlation was observed between the temperatures and enthalpies of crystallization of the mixtures, which could be used to establish the composition of a mixture between sesame and rapeseed oil. Information about these parameters could increase the possibilities for the commercial use of the investigated oils.